Cultural Considerations in the Treatment of Eating Disorders among Racial/Ethnic Minorities: A Systematic Review. (June 2021) - Acle, Ashley; Cook, Brian J.; Siegfried, Nicole; Beasley, Tammy
Eating disorders (ED) prevalence is rising among ethnic and racial minority groups, yet disparities persist in treatment seeking, and effectiveness. The purpose of this systematic review was to summarize works that provide theoretically grounded and empirically evidenced clinical recommendations for the inclusion of culture in the treatment of eating disorders in non-white individuals. Thirty one articles revealed the following 11 core recommendation themes for how to effectively address culture in ED treatment: use culturally sensitive interventions; address barriers to treatment; understand patients within their cultural context; explore the impact of culturally contextual factors; assume a collaborative, curious therapeutic stance; understand nuances that impact clinical presentations; explore family/social supports; provide education/psychoeducation; explore ethnic identity, acculturation and acculturative stress; become educated about working with ethnic and racial minorities; and use a culturally flexible diagnostic model. Consolidating these recommendations evidenced from the literature fills a gap relevant to ED treatment and provides empirically derived, culturally-accommodating guidance on how future studies may include ethnic and racial considerations when developing treatment approaches and/or evaluating outcomes.